(untitled) (Bangladesh Journal of Medical Science, 2022)
Background: Multiple Sclerosis is an inflammatory demyelinating disease having varied manifestations in terms of clinical featuresand radiological features. Rarely it may present as a large demyelinating lesionwith accompanying edema and mass effect, thereby simulating an intracranial tumor, known as Tumefactive Demyelination. Symptoms are usually related to the pressure of a focal mass lesion. When it manifests in a patient without pre-existing MS, it poses a diagnostic challengeas it may mimic a neoplasm, infarct or abscess. Thus, it is essential to recognize this rare clinical entity for proper patient management. Case Presentation: We report here a case of 40 years old female who presented with right sided hemiparesis. The initial brain imaging (CT) suggested left parietal lobe lesion suggestive of glioma. But MRI of the brain showed a cortical based lesion in left parietal lobe in parasaggital location which appeared hyperintense on both T2WI and FLAIR sequences. Further evaluation by MR spectroscopy suggested the lesion to be tumefactive demyelination. She was administered IV Methylprednisolone (1gm daily for 5 days) and responded well to treatment. The characteristic magnetic resonance findings of the patient, its acute onset, and its clinical improvement after corticosteroid therapy finally set the diagnosis of Tumefactive Demyelination. Conclusion: Tumefactive demyelinating lesions pose a unique diagnostic challenge in defining differential diagnosis and management and should always be considered in young patients presenting with tumour like lesions on imaging. Bangladesh Journal of Medical Science Vol. 21 No. 04 October’22 Page : 931-934